2016
DOI: 10.5897/ajb2016.15323
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of biomass production of Acetobacter pasteurianus KU710511 as a potential starter for fruit vinegar production

Abstract: The objective of the present work was first the isolation of novel acetic acid bacteria strains from natural Moroccan habitats, and then, the evaluation of their ability to produce microbial starters for vinegar production on a large scale. The strains were isolated from figs, dates, cactus, and traditional fruit vinegars. Four strains, selected from a total of 63 isolates, were confirmed as belonging to Acetobacter species according to biochemical and molecular studies based on 16s rRNA sequence analysis. Ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…From more than 60 isolates, three microbial strains were selected to carry out experiments aimed at the preparation of natural table olives. These strains, namely : Lactobacillus plantarum S1, Saccharomyces cerevisiae LD01 and Acetobacter pasteurianus KU710511 (CV01) were identified using biochemical and molecular techniques and characterized in previous studies (Mounir et al, 2018;Mounir et al, 2016a;Mounir et al, 2016b;Mounir et al, 2016c) The determination of chloride, titratable acidity, pH, and counts of LAB, yeasts and AAB were carried out using the methods described in the Material and methods section. Then, samples were presented to tasters to evaluate their organoleptic quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From more than 60 isolates, three microbial strains were selected to carry out experiments aimed at the preparation of natural table olives. These strains, namely : Lactobacillus plantarum S1, Saccharomyces cerevisiae LD01 and Acetobacter pasteurianus KU710511 (CV01) were identified using biochemical and molecular techniques and characterized in previous studies (Mounir et al, 2018;Mounir et al, 2016a;Mounir et al, 2016b;Mounir et al, 2016c) The determination of chloride, titratable acidity, pH, and counts of LAB, yeasts and AAB were carried out using the methods described in the Material and methods section. Then, samples were presented to tasters to evaluate their organoleptic quality.…”
Section: Resultsmentioning
confidence: 99%
“…The microbiological, physicochemical and sensory analyses carried out demonstrated the possibility of introducing a new process for producing natural table olives. In this method, we used a starter composed of two strains, namely Acetobacter pasteurianus KU710511 (CV01) and Lactobacillus plantarum S1 under the optimal conditions of AAB growth as reported by Mounir et al, (2016b) with 6% NaCl and alternating aeration of 8 hours/day.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the Carr medium, the production of the acid in the medium by strain can be seen in form of clearing of opacity of medium or the colour change of bromocresol green confirms that the isolate is Acetobacter species. Sharafi et al, (2010); Mounir et al, (2016) had reported that color change of the indicator bromocresol green in the medium from green to yellow confirm that the isolate is Acetobacter. The production of acid acetic of this strains was previously determined by Ouattara et al, (2018), where it was shown that these strains had the capacity to produce a high concentration of acetic acid and the highest was found with strain CRSBAN-BVA1.…”
Section: Discussionmentioning
confidence: 99%
“…Prefermented mango were transferred in a GYEA enrichment medium containing of glucose 2% (w/v), yeast extract 1% (w/v), ethanol 2% (v/v) and acetic acid 1% (v/v). Samples were incubated under agitation (120 rpm) at room temperature (30°C) for one week (Mounir et al, 2016). A volume of 100 μl from different dilutions were inoculated in GYC solid medium (10% glucose, 1.0% yeast extract, 2.0% calcium carbonate, 1.5% agar, pH 6.8) supplemented with 100 mg l -1 of Cycloheximide and nystatine were to inhibit the growth of fungi and lactic acid bacteria, respectively (Sharafi et al, 2010;Kadere et al, 2008).…”
Section: Screening Of Acetic Acid Bacteria (Aab)mentioning
confidence: 99%